Evaluation of Protective Equipment Used Among Motorbike Riders - Stiles, Roxanne; Benge, Clint; Stiles, P.J.; Dong, Fanglong; Ward, Jeanette; Ablah, Elizabeth; Haan, James M. (Kansas Journal of Medicine, 2019)
Introduction. This study compared outcomes between patients injured at a motorbike track, which requires riders to follow safety equipment guidelines, and those involved in recreational riding where safety equipment usage is voluntary. Methods. A retrospective review was conducted of all patients presenting with motorbike-related injuries at an American College of Surgeons verified level-I trauma center between January 1, 2009 and December 31, 2013. Data collected included demographics, injury details, safety equipment use, hospitalization details, and discharge disposition. Comparisons were made regarding protective equipment usage. Results. Among the 115 patients admitted, more than half (54.8%, n = 63) were injured on a motorbike track, and 45.2% (n = 52) were injured in a recreational setting. The majority of patients were male (93.9%), Caucasian (97.4%), and between the ages of 18 to 54 (64.4%). Helmet usage was higher among track riders (95.2%, n = 60) than recreational riders (46.2%, n = 24, p < 0.0001). Comparisons of injury severity and outcomes between those who wore protective equipment and those who did not were not significant. Conclusions. Even though track riders wore protective equipment more than recreational riders, there was no difference between the groups regarding injury severity or hospital outcomes. These results suggested that motocross riders should not rely on protective equipment as the only measure of injury prevention. Kans J Med 2018;11(2):44-47.